Market Predictability of ECB Policy Decisions : A Comparative Examination - Ross, Kevin (IMF Working Papers; Working Paper ;, 2002)
Many surveys of the ECB's monetary framework emphasize the inability of financial markets to correctly predict monetary policy decisions. At the same time, these surveys of financial market participants have given relatively high marks to the United States Federal Reserve and the Bank of England on their ability to be understood by financial markets. Against this background, this paper examines the ability of financial markets to correctly anticipate these three central bank policy decisions over the first 3 1\2 years of the ECB. The paper relies on calculations that market participants employ in anticipating policy changes and on term structure regressions that provide ex post evidence of market surprises. While the results suggest that all three central banks are broadly predictable, markets have had difficulty anticipating large changes and cuts in ECB policy interest rates. These surprises may be tied to the large number of policy meetings, particular characteristics of the EONIA money market, and the unique circumstances of the ECB. An added factor may be the absence of a consistent policy on communicating the current stance-if any-of the ECB's policy bias on the future direction of interest rates.